The Prudential Rationality of Risking Traumatic Brain Injury in Dangerous Sport: A Parfitian Defense - Eric Gilbertson (Philosophies, 2025)
It is an open question whether participation in dangerous sports is prudentially rational given the high risk of traumatic brain injury they involve. This paper explores the merits of one attempt to rationalize participation in dangerous sport, which is based on Derek Parfit’s idea that it is rational for you to care less about the well-being of your future selves the more distant they are, because time diminishes the degree of their psychological connectedness to your present self. I respond to two sets of concerns about this defense of dangerous sport. First, there are concerns that the Parfitian defense is too weak to justify taking such serious risks as dangerous sport involves—specifically, objections based on an appeal to the overall shape of one’s life, as well as objections from self-directed duties. Second, there are concerns that the Parfitian defense would prove too much—specifically, that it would rationalize generally reckless risk-taking for fun; and that it would make one exploitable. I show that none of these objections succeeds, and I conclude that the Parfitian defense remains tenable.